Equalizing income versus equalizing opportunity: A comparison of the United States and Germany - Ingvild Almås (Luxembourg Income Study (LIS), 2008)
Germany has lower posttax income inequality than the United States and hence is doing better according to a strict egalitarian fairness ideal. On the other hand, the United States is doing better than Germany according to a libertarian fairness ideal, which states that people should be held fully responsible for their income. However, most people hold intermediate (responsibility-sensitive) positions, and hence it is interesting to study and compare fairness according to these positions. We find that the ranking of the two countries according to the intermediate positions depends on the treatment of the unexplained variation in the income equation. If we hold people responsible for the residual, the United States is considered fairer than Germany for all levels of responsibility sensitivity. If we, however, demand compensation for the residual, Germany is fairer than the United States for all levels of responsibility. The latter may be seen as the preferred approach as it follows a `benefit of the doubt' strategy.
Keywords: 330; Einkommensumverteilung; Steuergerechtigkeit; Verteilungsgerechtigkeit; Vergleich; Deutschland; USA